2012
DOI: 10.1111/j.1537-2995.2012.03629.x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic risk factor for low serum ferritin levels in Danish blood donors

Abstract: A frequent polymorphism in BTBD9 was significantly associated with serum ferritin. This polymorphism has previously been associated with RLS, but not low iron stores in blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…However, each additional G allele resulted in a non- We also identified studies in the Chinese population that have observed rs855791 and rs4820268 polymorphisms as genetic risk factors for developing anaemia, iron deficiency and iron deficiency anaemia Gan et al 2012). We additionally identified another study conducted among Danish blood donors that has observed that the T and G alleles of rs855791 and rs4820268, respectively, are not associated with low serum ferritin (Sorensen et al 2012).…”
Section: Tmprrs6 Variants Not Eligible For Meta-analysismentioning
confidence: 99%
“…However, each additional G allele resulted in a non- We also identified studies in the Chinese population that have observed rs855791 and rs4820268 polymorphisms as genetic risk factors for developing anaemia, iron deficiency and iron deficiency anaemia Gan et al 2012). We additionally identified another study conducted among Danish blood donors that has observed that the T and G alleles of rs855791 and rs4820268, respectively, are not associated with low serum ferritin (Sorensen et al 2012).…”
Section: Tmprrs6 Variants Not Eligible For Meta-analysismentioning
confidence: 99%
“…Thus, in a recent study, we investigated the prevalence of five specific single‐nucleotide polymorphisms (SNPs) in TMPRSS6 , TF, and BTBD9 in two groups with 650 Danish blood donors in each group with low and high iron stores, respectively. We identified a SNP in BTBD9 not previously described as being associated with low iron stores; however, our study was not powered to detect small effects of the genotypes on ferritin level, and small but clinically relevant effects could thus go undetected.…”
mentioning
confidence: 76%
“…Ferritin was measured in thawed EDTA‐anticoagulated plasma samples from 18,070 participants using a commercially available assay on an automated system (Ortho Vitros 5600, Ortho Clinical Diagnostics, Rochester, NY). Based on the results from our previous report and on a literature search, we identified SNPs in the following genes: 1) TMPRSS6 —rs855791; 2) BTBD9 —rs9357271; 3) TF —rs2280673 and rs11830084; and 4) HFE —rs1800562 and rs1799945. DNA was extracted and analyzed by LGC genomics extraction and genotyping service (Hoddesdon, Herts, UK).…”
Section: Methodsmentioning
confidence: 99%
“…5 Another BDBT9 allelic variant relates to RLS/WED diagnosis, 3 increased PLMS, 6 and greater decreases in peripheral iron stores with blood donations. 7 Functional relation of BTBD9 has been further indicated by findings of increased peripheral iron for a BDBT9-mutant mouse 8 and murine ventral midbrain iron content associated with a quantitative trait loci that includes BDBT9. 9 Besides these findings relating in general BDBT9 to iron deficiency in RLS/WED, there has been no significantly substantial discovery of potential genetics pathways to RLS/WED pathophysiology.…”
Section: Genetics and Restless Leg Syndrome/willis-ekbom Disease Pathmentioning
confidence: 99%